Synthesis and Biological Screening of Some New 3[2-Methyl-1,2- dihydropyrimido[1,2c]benzimidazole-1-thionyl]-6,8-dibromo- 2-substituted-3H-quinazolin-4-one - Srinivasan, N.; Balaji, Anna; Nagarajan, G.; Suthakaran, R.; Kumar, Yashwanth; Jagadesh, D. (Asian Journal of Chemistry, 2010)
In this paper, the synthesis and characterization of substituted quinazolin-4-ones from 3-amino-2-methyl-1,2-dihydropyrimido-( 1,2-c)- benzimidazole-1-thione are reported. The synthesized compounds were also screened for their analgesics and antiinflammatory and diuretic activity.